파장별 야간 조사에 따른 ‘거봉’ 포도의 품질 및 생산량 - 박희승(Hee-Seung Park); 김준혁(JunHyeok Kim); 박요섭(YoSup Park); 권용희(YongHee Kwon); 정명희(MyungHee Jung) (Weon'ye gwahag gi'sulji, 2017)
This study was conducted to estimate the light pollution damage caused by night-break lighting in 'Kyoho' grapes. Night irradiation was performed every night for four hours (10 p.m. to 2 a.m.) from the full bloom to the harvest stage using red, blue, and white lamps as artificial light. Fruit yield, soluble solid content, anthocyanin content, and chlorophyll a content were affected by night irradiation. The soluble solid content of the control was $17.5^{°}Brix$, approximately $1^{°}Brix$ higher than the red ($16.4^{°}Brix$), blue ($16.2^{°}Brix$), and white light treated grapes ($16.3^{°}Brix$). The anthocyanin content of the skin was also higher in the control at $4.08μg{·}cm^{-2}$ compared to the red ($3.14μg{·}cm^{-2}$), blue ($2.47μg{·}cm^{-2}$), and white ($2.82μg{·}cm^{-2}$) light treated samples. On the other hand, the chlorophyll a content of the control was the lowest at $0.268μg{·}cm^{-2}$ as compared with the red ($0.339μg{·}cm^{-2}$), blue ($0.345μg{·}cm^{-2}$), and white ($0.372μg{·}cm^{-2}$) light treated samples. Considering that higher soluble solid contents, higher accumulation of anthocyanin, and lower chlorophyll a contents are factors involved in fruit maturation, night irradiation may delay fruit maturation and red light treatment may result in decreased yield. Our results confirmed that night-break lighting regardless of the wavelength provoked light pollution in 'Kyoho' grapes. Therefore, fruit maturation may be poor in the presence of artificial light, including streetlamps, in neighboring vineyards. 본 연구는 '거봉' 포도 재배시 야간의 빛 공해에 따른 피해를 예측하기 위하여 실시하였다. 야간 조사는 만개기부터 수확기까지 인공 광원으로 적색, 청색, 백색 램프를 사용하여 매일 오후 10시부터 오전 2시까지 4시간동안 조사하였다. 야간 조사는 생산량을 비롯하여 가용성 고형물 함량, anthocyanin, chlorophyll a 함량에 영향을 미치는 것으로 조사되었다. 무처리구의 가용성 고형물 함량은 $17.5^{°}Brix$로 야간에 빛을 조사한 적색광, 청색광, 백색광 처리구의 16.4, 16.2, $16.3^{°}Brix$에 비해 $1^{°}Brix$ 이상 높았으며, 과피의 anthocyanin 함량 또한 무처리구가 $4.08μg{·}cm^{-2}$로 적색광, 청색광, 백색광 처리구의 3.14, 2.47, $2.82μg{·}cm^{-2}$ 보다 높은 것으로 조사되었다. 반면에 chlorophyll a 함량은 무처리구가 $0.268μg{·}cm^{-2}$로 적색광, 청색광, 백색광 처리구의 0.339, 0.345, $0.372μg{·}cm^{-2}$와 비교하여 가장 낮았다. 결과적으로, 당의 증가와 anthocyanin의 축적 및 chlorophyll의 감소는 과실 성숙에 수반된 현상이라는 점을 고려할 때, 야간 조사는 '거봉'의 암기를 중단시켜 과실의 성숙 과정을 지연시키며 적생광 처리는 생산량 감소를 수반하였다. 따라서 광파장에 관계없이 야간조사에 의한 빛공해가 나타나는 것으로 확인되었으며, 가로등을 비롯한 야간 조명이 설치된 지역에 인접한 포도원의 경우 과실의 성숙이 불량해 질 수 있는 것으로 판단된다.